Subject Position and Manifestations of Workplace Followership (Journal of Organizational Psychology, 2021)
This study examined three constructs of followership in the workplace context. Adopting a qualitative design and a conceptual framework based on the theories of subject positioning and sense-making, we explored organizational actors’ underlying followership beliefs and meaning-making processes, and how they enact those beliefs and meanings in the context of follower-leader relationship. We analyzed interview data along the constructs followership positionality, sense-making and enactment. The findings indicate that followers situate their relationships in the evolving context of follower-leader relationship dynamics. They continuously engage in identity work and sense-making process to understand power and personal agency and adjust their engagements according to the constraint of authority hierarchy and the realms of workplace engagement possibilities, and opportunities for future career growth.
Keywords: organizational psychology; subject positionality; workplace followership; followership enactment; follower sense-making